2019
DOI: 10.1111/mpp.12902
|View full text |Cite
|
Sign up to set email alerts
|

Inositol hexakisphosphate biosynthesis underpins PAMP‐triggered immunity to Pseudomonas syringae pv. tomato in Arabidopsis thaliana but is dispensable for establishment of systemic acquired resistance

Abstract: Phytic acid (inositol hexakisphosphate, InsP6) is an important phosphate store and signal molecule necessary for maintenance of basal resistance to plant pathogens. Arabidopsis thaliana (‘arabidopsis’) has three genes encoding myo‐inositol phosphate synthases (IPS1–3), the enzymes that catalyse conversion of glucose‐6‐phosphate to InsP, the first step in InsP6 biosynthesis. There is one gene for inositol‐(1,3,4,5,6)‐pentakisphosphate 2‐kinase (IPK1), which catalyses the final step. Previously, we showed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 66 publications
0
13
2
Order By: Relevance
“…These results indicate that the enhanced susceptibility of ips2 and ipk1 is not related to low SA levels, but could be caused by the disruption of InsP 6 biosynthesis ( Murphy et al, 2008 ). Further studies of the ipk1 mutant and of loss-of-function mutants of another IPS isoform ( IPS3 ) confirmed an involvement of InsP 6 in basal pathogen responses ( Poon et al, 2020 ). While displaying a higher susceptibility to Pst than wild-type plants, when the ips2 , ips3 , and ipk1 mutants were assessed for SAR acquirement, no impairment was detected.…”
Section: Inositol Pyrophosphate Kinases and Their Role In The Adaptio...mentioning
confidence: 80%
See 2 more Smart Citations
“…These results indicate that the enhanced susceptibility of ips2 and ipk1 is not related to low SA levels, but could be caused by the disruption of InsP 6 biosynthesis ( Murphy et al, 2008 ). Further studies of the ipk1 mutant and of loss-of-function mutants of another IPS isoform ( IPS3 ) confirmed an involvement of InsP 6 in basal pathogen responses ( Poon et al, 2020 ). While displaying a higher susceptibility to Pst than wild-type plants, when the ips2 , ips3 , and ipk1 mutants were assessed for SAR acquirement, no impairment was detected.…”
Section: Inositol Pyrophosphate Kinases and Their Role In The Adaptio...mentioning
confidence: 80%
“…This is because studies showing an involvement of InsPs and PP-InsPs in SA-dependent immunity have in part contradictory outcomes. Arabidopsis mutants disrupted in InsP 6 biosynthesis, for instance, showed increased susceptibility to bacterial, fungal and viral infections ( Murphy et al, 2008 ; Poon et al, 2020 ), as well as to cyst nematode infestation ( Jain, 2015 ). In fact, the Arabidopsis ips2 and ipk1 mutants defective in the activities of enzymes for the first and last steps in InsP 6 biosynthesis, respectively, were similarly susceptible to microbial pathogens than NahG -transgenic lines and to sid2 mutants, both of which are unable to accumulate normal levels of SA ( Murphy et al, 2008 ).…”
Section: Inositol Pyrophosphate Kinases and Their Role In The Adaptio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Murphy et al (2008) however did not find noticeable change either in the basal SA levels or its increase upon avirulent pathogen challenge in ipk1-1 . Further, although Poon et al (2020) did not measure the endogenous expression levels of FRK1 or other PTI markers, their induction upon PAMP-treatment was not affected in ipk1-1 . Ma et al (2017) in contrast showed impaired induction of FRK1 and other PTI responses in ipk1-1 (also in mips1 and mips2 ) with PAMP-exposure.…”
Section: Discussionmentioning
confidence: 93%
“…Defenses against the cyst nematode is also reduced in the ipk1-1 plants (Jain, 2015). Recently, it was shown that while ipk1-1 plants remain deficient in induction of local resistance, PTI hallmarks such as intracellular Ca 2+ spike, ROS production, and upregulated expression of responsive markers remained comparable to wild-type plants (Poon et al ., 2020). An earlier study though contrastingly claimed that induction of PTI markers upon PAMP-treatment are deficient in ipk1-1 (Ma et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%